Defermination of landscape geographycal impact into household income of herders in Mongolia - B, Shoshvandan; L, Bayasgalan; Shan, Hai (Mongolian Journal of Agricultural Sciences, 2018)
Our study the goal is to identify the geographical impacts of Mongolian herder’s family income. This will examine the relationship between nature and geographical features and the business of Mongolian herders.The research that We have determined the result to achieve our goals the study was conducted from the Gobi region to Tugrug Uburkhangai district, Steppe region from Taragt Uburkhangai district, hight mountain zone Khujirt in Uburkhangai district, forest steppe zone Undur-Ulaan and Khairkhan in Arkhangai aimag, from the dry steppe zone Bulgan district, Gurbanbulag district was selected. The herders family gain their income from mutton, goat wool, camel wool in Gobi region and mutton, goat wool in steppe region and horse, cow, mutton and goat meat, goat wool, dairy products in high mountain region and cow, horse, sheep, goat meat, daily products in forest steppe region and cow, horse, sheep, goat meat, daily products in dry steppe region. Монгол малчдын өрхийн орлогод байгаль газарзүйн нөлөөг тодорхойлох нь Хураангуй: Монгол малчдын өрхийн орлогод газарзүйн нөлөөлөх нөлөөлөлийг тодорхойлохын тулд байгаль, газарзүйн онцлог болон монгол малчдын малчдын эрхэлж байгаа аж ахуй хоорондын харилцан хамаарлыг судлахад бидний судалгааны зорилго оршино. Бид зорилгоо биелүүлэхийн тулд судалгааны объёоктоо говийн бүсээс Өвөрхангай аймгийн Төгрөг, хээрийн бүсээс Өвөрхангай аймгийн Тарагт, өндөр уулын бүсээс Өвөрхангай аймгийн Хужирт, ойт хээрийн бүсээс Архангай аймгийн Өндөр-Улаан, Хайрхан, хуурай хээрийн бүсээс Булган аймгийн Гурван булаг сумыг сонгон авч судалгаа хийж, үр дүнг тодорхойлсон. Говийн бүсэд хонины мах, ямааны ноолуур, тэмээний ноос, хээрийн бүсэд хонины мах, ямааны ноолуур, өндөр уулын бүсэд бог, бодын мах, ямааны ноолуур, цагаан идээ, ойт хээрийн бүсэд бог, бодын мах, цагаан идээ, хуурай хээрийн бүсэд бог, бодын мах, ямааны ноолуураас өрхийнхөө орлогыг бүрдүүлж байна. Түлхүүр үг: Байгалийн бүс, бүслүүр, газарзүйн нөлөөлөл, аж ахуй, өрхийн орлого